Copulas, Auxiliaries and Notional Verbs - Драздаускас, А. (Kalbotyra, 1976)
The problem of copulas and the classification of verbs into copulas, auxiliaries and notional verbs is discussed. The concept of “linking function” is introduced. The existence of pure copulas and auxiliaries is argued on the basis that any verb can fulfil the linking function and always retain its concrete lexical meaning to a greater or smaller extent.